Stable Vacancy-Rich Sodium Vanadate as a Cathode for High-Performance Aqueous Zinc-Ion Batteries - Zhibo Xie; Yongru Qu; Fuwei Kong; Ruizheng Zhao; Xianfen Wang (Nanomaterials)
Vanadium-based cathodes are promising for aqueous zinc-ion batteries (ZIBs) due to the large interlayer distance. However, the poor stability of electrode materials due to the dissolution effects has severely hindered the commercial development. To address this challenge, we propose an in situ NH4+ pre-intercalation strategy to enhance the electrochemical performance of Na0.76V6O15 (NaVO), thereby optimizing its structural stability and ionic conductivity. Moreover, NH4+ pre-intercalation introduced a large number of oxygen vacancies and defects into the material, causing the reduction of V5+ to V4+. This transformation suppresses the dissolution and enhances its conductivity, thereby significantly improving the electrochemical performance. This modified NaNVO cathodes deliver a higher capacity of 456 mAh g−1 at 0.1 A g−1, with a capacity retention of 88% after 140 cycles and a long lifespan, maintaining 99% of its initial capacity after 2300 cycles. This work provided a new way to optimize the cathode for aqueous zinc-ion batteries.